Unilateral ablation of trunk superficial neuromasts increases directional instability during steady swimming in the yellowtail kingfish Seriola lalandi. Issue 3 (31st July 2014) - Yanase, K.; Herbert, N. A.; Montgomery, J. C.
<x xml:space="preserve">Abstract</x> Detailed swimming kinematics of the yellowtail kingfish Seriola lalandi were investigated after unilateral ablation of superficial neuromasts (SNs). Most kinematic variables, such as tail‐beat frequency, stride length, caudal fin‐beat amplitude and propulsive wavelength, were unaffected but lateral amplitude at the tip of the snout (A0) was significantly increased in SN‐disrupted fish compared with sham‐operated controls. In addition, the orientation of caudal fin‐tip relative to the overall swimming direction of SN‐disrupted fish was significantly deflected (two‐fold) in comparison with sham‐operated control fish. In some fish, SN disruption also led to a phase distortion of the propulsive body‐wave. These changes would be expected to increase both hydrodynamic drag and thrust production which is consistent with the finding that SN‐disrupted fish had to generate significantly greater thrust power when swimming at ≥1·3 fork lengths (LF) s−1. In particular, hydrodynamic drag would increase as a result of any increase in rotational (yaw) perturbation and sideways slip resulting from the sensory disturbance. In conclusion, unilateral SN ablation produced directional instability of steady swimming and altered propulsive movements, suggesting a role for sensory feedback in correcting yaw and slip disturbances to maintain efficient locomotion.